Environmental Accounting and its Impact on the Economy: An Applied Study on Industrial Establishments in Jeddah Governorate in the Kingdom of Saudi Arabia - Abo Hussain, Maha Abbas (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to shed light on the impact of environmental accounting measured in (environmental cost accounting, environmental sustainability, and environmental policies) in industrial enterprises on the economy in the Kingdom of Saudi Arabia. To achieve the objectives of the study, the study relied on the descriptive-analytical approach, due to its suitability of the nature of the study, as well as the questionnaire tool was distributed to the study sample using random sample method, where (200) questionnaires were distributed to financial managers working in industrial enterprises in the Kingdom of Saudi Arabia in the Jeddah, the final study sample was (96) questionnaires. The results of the study showed that there is an impact of environmental accounting measured by (environmental cost accounting, environmental sustainability, and environmental policies) in industrial companies on the economy, individually and collectively. The study came out with a set of recommendations, the most important of which is the necessity of developing local standards or adopting international standards for environmental disclosure in other sectors in general and the state’s contribution to providing quantifiable environmental data and raising the limitations imposed on companies in particular in order to follow and encourage environmental laws.